Community Empowerment Aware of Health Model - Miftahul Munir; Suhartono Suhartono (Jurnal Ners, 2016)
Introduction: Health degree influenced by several factors and the offspring of the Ministry of Health and behavior and the environment. The behavior and environmental factors have contributed most in improving the degree of community health. The purpose of this research is to prove and analyzing the influence of the characteristics of the individual, self efficacy and team work against the commitment and productivity of health cadres. Methods: This research method using analytically research with explanatory research approach. Samples in this research totaled 200 respondents. The data was taken using simple random sampling. The collection of data use of the questionnaire, interview and observation. Data analysis was used the statistical test Partial Least Square (PLS). Result: Research results show the influence of the productivity variable health cadres of economic investment health is of 0,291 with the value of T-statistic of 4,645, where the value of the T-statistic was greater than 1.96 which means the productivity of health cadres significant effect of economic investment health, this shows the influence of the productivity of health cadre of economic investment health was positive, it means that when the productivity of health cadres are higher then the economic investment will also increasingly good health. Discussion: This research can serve as a reference for the district government of Tuban in increasing the degree of community health. Improving the health of the community must be done via promotif efforts and preventive measures through productivity program health cadres. The productivity of health cadres have an important role in efforts to improve the health of the community so that the government can save the funds for health or economic investment of health.